2012
DOI: 10.1177/0954410011414321
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic integration of computational fluid dynamics and experimental fluid dynamics for ground effect aerodynamics studies

Abstract: This article highlights the 'synergistic' use of experimental fluid dynamics (EFD) and computational fluid dynamics (CFD), where the two sets of simulations are performed concur rently and by the same researcher. In particular, examples from the area of ground effect aero dynamics are discussed, where the major facility used was also designed through a combination of CFD and EFD. Three examples are than outlined, to demonstrate the insight that can be obtained from the integration of CFD and EFD studies. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Furthermore, to determine the performance variations of the wing as a result of its deflection, predicting the forces and pressure variation is expected to be the most vital parameters. Previous studies 16,[20][21][22][23][24][25] have already demonstrated the effectiveness of RANS modelling for predicting the aerodynamic loads, pressure distribution and the time average flow structures of a downforce producing wing in ground effect when using either the k2v SST 21 or k2e realisable. 26 The choice of the turbulence model is further described in section 2.6.1.…”
Section: Aerodynamic Modelmentioning
confidence: 99%
“…Furthermore, to determine the performance variations of the wing as a result of its deflection, predicting the forces and pressure variation is expected to be the most vital parameters. Previous studies 16,[20][21][22][23][24][25] have already demonstrated the effectiveness of RANS modelling for predicting the aerodynamic loads, pressure distribution and the time average flow structures of a downforce producing wing in ground effect when using either the k2v SST 21 or k2e realisable. 26 The choice of the turbulence model is further described in section 2.6.1.…”
Section: Aerodynamic Modelmentioning
confidence: 99%
“…This is an unsteady aerodynamic problem. In the past, for such problems, the aerodynamic interference between the prototype and the environment in different scenarios were generally obtained through CFD [ 2 , 3 , 4 ] and wind tunnel experiments [ 5 , 6 , 7 ]. However, CFD simulation and wind tunnel experiments also have certain limitations.…”
Section: Introductionmentioning
confidence: 99%
“…As recently as 2006, it was acknowledged in two separate reviews of racing vehicle aerodynamics that the physics associated with the interaction of the wings and the front wheels remained poorly understood 3 and that more research was required on the topic. 4 Downforce-producing wings [5][6][7][8][9][10][11][12][13][14][15][16] and wheels [17][18][19][20][21] as individual components have been relatively thoroughly studied in the last 20 years, with an increasing focus on using numerical approaches to understand, in particular, the complexities of wheel wakes which are not easily revealed from wind-tunnel testing alone.…”
Section: Introductionmentioning
confidence: 99%